Optimal Technology Selection and Operation of Bio-methane CHP Units for Commercial Buildings - Acha,Izquierdo S; Cedillos,D; Shah,N (ASHRAE, 2016)
This paper explores the optimal implementation of bio-methane fuelled combined heat and power (CHP) systems to satisfy heat and electricity demands ofcommercial buildings; with the overarching goal of making cost-effective investments and decarbonizing building operations. The research work consisted inthe development of a CHP technology selection and operation (TSO) optimization model. Its results can be utilized to develop a strategy for investment inbio-methane CHP projects for a portfolio of buildings. The TSO model enables a new approach for the selection and operation of CHP units thatencompasses whole life costing, carbon emissions as well as real-time energy prices and demands, providing a more comprehensive result than current methods.Utilizing historic metered energy demands, projected energy prices and a portfolio of available CHP technologies, the mathematical model simultaneouslysolves for an optimal CHP unit selection and operational strategy for a determined building based on a preferred objective: minimizing cost, minimizingGHG emissions, or a mix of both. Results of this model prove that attractive cost and emissions savings are possible through the optimal selection andoperation of CHP technologies fuelled by bio-methane